Toxicity from ingestion of Jatropha curcas ('saboo dum') seeds in Thai children - Chulathida Chomchai (2015)
Jatropha curcas is widely cultivated in Thailand, the seeds of which yield high quality oil used for biodiesel production. Toxicity due to ingestion of Jatropha curcas has become more common among children due to the close proximity between cultivation and residential areas. We report 10 calls made over a 40-month period to the Siriraj Poison Control Center involving 75 children ages 2- 14 years who experienced toxicity after ingesting various amounts of Jatropha beans. The amounts ingested, presenting symptoms, pertinent laboratory findings and their collective dispositions are reported. A brief review of recent published literature on toxicity due to ingestion of Jatropha curcas was also done.